Implikasi Kekuasaan terhadap Konstitusi dan Pilkada di Era Otonomi Daerah - Arifuddin Siraj (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This paper aims to find out the impact and implications of power in the implementation of local autonomy in Indonesia. This study analyzes the constitutional and electoral changes as a form of good governance principle. The results of the study show that the implications and impacts of direct election in direct elections give the nuances of violating the constitution frequently. Similarly, the tendency to interpret the rules according to the will of the regional authorities. So that impact on the emergence of horizontal conflict society. Similarly, a growing number of interest conflicts arise, also giving extra work of the Constitutional Court (MK) to confirm to the constitution. This is exacerbated by the political elite who make politics as a means to seize power so often the political substance deviated from its true value. And this study shows that the election results are not optimal and make local leaders show behavior that is not pro-society with the growth of corruption. This article suggests a serious effort to address it by providing character education for local leaders with a nuanced sense of religious value and local wisdom.